Bladder Rupture as a Complication of Circumcision following Total Subcoronal Urethral Ligation - Asal Hojjat; Sorena Keihani; Amir Hassan Mahboubi; Abdol-Mohammad Kajbafzadeh (Case Reports in Urology)
Circumcision is one of the most commonly performed procedures and generally is considered a safe and minor surgery. However, serious and catastrophic complications may sometime occur if adequate attention is not paid to all aspects of this procedure. Bleeding is the most common early complication of circumcision and sometimes is controlled by applying sutures. We hereby report a case of urethral obstruction after deep suturing of the bleeding site performed at a district center that led to bladder rupture as an exceedingly rare complication following circumcision.